The Welfare Effects of Law Enforcement in the Illegal Money Lending Market - Kaiwen Leong; Huailu Li; Nicola Pavanini; Christoph Walsh (Institute of Labor Economics (IZA), 2022)
We estimate a structural model of borrowing and lending in the illegal money lending market using a unique panel survey of 1,090 borrowers taking out 11,032 loans from loan sharks. We use the model to evaluate the welfare effects of alternative law enforcement strategies. We find that a large enforcement crackdown that occurred during our sample period raised interest rates, lowered the volume of loans, increased the lenders' unit cost of harassment, decreased lender profits, and decreased borrower welfare. We compare this strategy to targeting borrowers and find that targeting medium-performing borrowers is the most effective at lowering lender profits.
Keywords: K42; G51; 330; illegal money lending; loan sharks; law enforcement; crime